2015
DOI: 10.1016/j.gendis.2015.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Platelets and platelet alloantigens: Lessons from human patients and animal models of fetal and neonatal alloimmune thrombocytopenia

Abstract: Platelets play critical roles in hemostasis and thrombosis. Emerging evidence indicates that they are versatile cells and also involved in many other physiological processes and disease states. Fetal and neonatal alloimmune thrombocytopenia (FNAIT) is a life threatening bleeding disorder caused by fetal platelet destruction by maternal alloantibodies developed during pregnancy. Gene polymorphisms cause platelet surface protein incompatibilities between mother and fetus, and ultimately lead to maternal alloimmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 192 publications
0
15
0
Order By: Relevance
“…Platelets, via their contributions to the "protein wave" and to the classical first and second waves of hemostasis, play key roles in the arrest of bleeding [ 31 ] . Thrombocytopenias caused by either genetic deficiencies [ 86 ] or autoimmune [ 87 - 89 ] and alloimmune responses lead to bleeding disorders [ 21 , 32 , 33 , 90 - 96 ] . However, the same platelet accumulation and coagulation may lead to thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets, via their contributions to the "protein wave" and to the classical first and second waves of hemostasis, play key roles in the arrest of bleeding [ 31 ] . Thrombocytopenias caused by either genetic deficiencies [ 86 ] or autoimmune [ 87 - 89 ] and alloimmune responses lead to bleeding disorders [ 21 , 32 , 33 , 90 - 96 ] . However, the same platelet accumulation and coagulation may lead to thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…The present study was performed in order to investigate the thrombosis of tumor-bearing mice using LDPI in combination with blood cell analysis. Platelets are essential mediators of the process of pathologic thrombosis (10). Previous experimental evidence has demonstrated that platelets support tumor metastasis (11).…”
Section: Introductionmentioning
confidence: 99%
“…PLTs are the primary mediators of pathological thrombosis [23]. Previous empirical evidence has shown that PLTs support tumor malignancy [24].…”
Section: Discussionmentioning
confidence: 99%